Computer Engineering and Technology 18th CCF Conference, NCCET 2014, Guiyang, China, July 29 -- August 1, 2014. Revised Selected Papers - Xu, Weixia; Xiao, Liquan; Li, Jinwen; Zhang, Chengyi; Zhu, Zhenzhen (Communications in Computer and Information Science, 2015)
This book constitutes the refereed proceedings of the 18th National Conference on Computer Engineering and Technology, NCCET 2014, held in Guiyang, China, during July/August 2014. The 18 papers presented were carefully reviewed and selected from 85 submissions. They are organized in topical sections on processor architecture; computer application and software optimization; technology on the horizon.